2010
DOI: 10.1007/s12124-010-9118-7
|View full text |Cite
|
Sign up to set email alerts
|

Empathy: From Mind Reading to the Reading of a Distant Text

Abstract: In the psychoanalytic literature empathy is commonly discussed as a form of "mind reading", which is deeply associated with the capacity to mirror the other's mental state. In this paper, I propose an alternative perspective on empathy as the process of reading a distant text. This perspective is illustrated through a Talmudic story and by weaving a thread between Bakhtin, Bion and Lacan. The paper concludes by pointing to the danger of empathy as a hidden form of projective identification that provides the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…By this I mean that, in exploring and charting the more ambiguous and uncertain regions of human experience, what is required-in the name of science-is a kind of literature. Along these lines, I have suggested that inquiry of this sort might be oriented toward feeling as well as thinking, thus supporting not only the customary epistemological aim of increasing knowledge and understanding but the ethical aim of increasing sympathy and compassion and the aesthetic aim of moving readers-that is, providing a means by which they might be dis-placed by the otherness of the text before them (Freeman 2003; see also, in this context, Neumann [2010]). Such science, which I earlier referred to as poetic science, can therefore provide readers the opportunity for much the same kind of felt engagement that works of literature can provide when they seek to disclose the deeper realities of experience.…”
Section: The Meaning Of "Science"mentioning
confidence: 95%
“…By this I mean that, in exploring and charting the more ambiguous and uncertain regions of human experience, what is required-in the name of science-is a kind of literature. Along these lines, I have suggested that inquiry of this sort might be oriented toward feeling as well as thinking, thus supporting not only the customary epistemological aim of increasing knowledge and understanding but the ethical aim of increasing sympathy and compassion and the aesthetic aim of moving readers-that is, providing a means by which they might be dis-placed by the otherness of the text before them (Freeman 2003; see also, in this context, Neumann [2010]). Such science, which I earlier referred to as poetic science, can therefore provide readers the opportunity for much the same kind of felt engagement that works of literature can provide when they seek to disclose the deeper realities of experience.…”
Section: The Meaning Of "Science"mentioning
confidence: 95%
“…Neuman ( 2010 ) makes a similar point in an investigation of the concept of empathy as a claimed function within the potentially therapeutic relationship of psychoanalysis. He takes as a starting point classic definitions of empathy from Heinz Kohut who suggested that “The best definition of empathy … is the capacity to think and feel oneself into the inner life of another person (Kohut, 1984 , p. 82) [and that] Empathy is a basic endowment of man” and an “introspection” into others (Kohut, 1959 , p. 144), a kind of “mind‐reading.” Against this understanding of empathy which is prevalent within nursing, Neuman proposes that the utterances and behavior—a cry or a grin perhaps—of another should be approached as an unfamiliar text.…”
Section: Sigmund Freudmentioning
confidence: 95%
“…However, this is not the case with Kohlhaas. As implied by Bakhtin, we should suspect even a moral deed launched from a purely transcendental perspective (Neuman, 2010). As we quickly learn from the story, Kohlhaas is not a social reformer.…”
Section: On Revengementioning
confidence: 97%